2021
DOI: 10.1186/s12955-021-01701-3
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and mental health among juveniles: role of strategies for coping with stress

Abstract: Background Mental health is an important aspect of the process of individual adaptation and development. The present study analysed the role played by resilience in mental health while taking into account both positive and negative indicators among juveniles. The aim of the first study (Study 1) is to analyse the relationship between resilience and the broadly understood mental health of juveniles admitted to youth education centres. Study 2 aimed to understand the direct and indirect role of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 109 publications
5
34
2
1
Order By: Relevance
“…However, the relationship was not moderated by the coping strategy employed. The finding of a positive correlation between resilience and well-being is consistent with relevant studies which reported resilience as contributing to one's positive wellbeing (Malkoc & Yalcin, 2015;Souri & Hasanirad, 2011;Chow et al, 2018;Yildirim & Arslan, 2020;Konaszewski et al, 2021;Chen, 2016).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the relationship was not moderated by the coping strategy employed. The finding of a positive correlation between resilience and well-being is consistent with relevant studies which reported resilience as contributing to one's positive wellbeing (Malkoc & Yalcin, 2015;Souri & Hasanirad, 2011;Chow et al, 2018;Yildirim & Arslan, 2020;Konaszewski et al, 2021;Chen, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…However, this present study showed that both approach and avoidant coping strategies did not moderate the relationships between resilience and well-being. While previous literature showed the moderating role of some coping strategies on the relationship between resilience, stress, burnout, and well-being or quality of life (Dardas & Ahmad, 2015;Connor-Smith & Compas, 2002;Malkoc & Yalcin, 2015;Konaszewski et al, 2021), there were also some studies that support the result of this study. For example, Kirsch (2014) found that neither adaptive nor maladaptive coping styles moderated the significant predictive relationship between body dissatisfaction and disordered eating attitudes when adjusting for disordered eating attitudes and BMI.…”
Section: Discussionsupporting
confidence: 57%
“…Nine cross-sectional studies and one longitudinal study examined resilience and psychopathology in the context of adverse childhood experiences (ACE) and negative life events [ 18 ▪ , 19 , 20 ▪ , 21 ▪ , 22 ▪ , 23 , 24 , 25 , 26 ▪ , 27 ]. Overall, these studies show that higher levels of resilience are associated with mental health.…”
Section: Part Ii: Systematic Literature Searchmentioning
confidence: 99%
“…Last, one study investigated the relationship of resilience with coping strategies in the context of negative life evens. In 253 juveniles sent to educational centers by a family court [ 27 ], resilience significantly predicted coping strategies, in particular active coping and seeking support from others. In addition, the relationship between resilience and mental wellbeing was mediated by seeking support from others and coping through discharging negative emotions.…”
Section: Part Ii: Systematic Literature Searchmentioning
confidence: 99%
“…Strengthening adolescents' internal and external resources and protecting them from risk factors and adverse experiences positively impact their potential to thrive and their mental health and well-being during adulthood. Previous studies have shown that timely interventions to strengthen adolescents' family and social resources and to decrease risk factor levels could prevent much of the disease burden in adulthood [3,4], and that strengthening resilience among young people leads to positive health outcomes [5].…”
mentioning
confidence: 99%